Sweet potato value chain in Kenya - Onyango, Kevin; Chege, Christine Gacheri Kiria; Polo, Carolina (2022)
Study on the sweet potato value chain in Kenya that revealed key strategies to reduce postharvest losses to improve food and nutrition security.